2013
DOI: 10.2174/1874192401307010113
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging on Indices of Oxidative Stress and Apoptosis in the Female Fischer 344/Nnia X Brown Norway/BiNia Rat Heart

Abstract: Oxidative-nitrosative stress may play a role in age-associated cardiovascular disease as implied by recent studies.However, limited research has been conducted using aged female rodent models. In this study, we examined hearts obtained from 6-, 26-, and 30-month old female Fischer 344/Nnia x Brown Norway/BiNia (F344xBN) rats in order to examine how aging affects levels of cardiac oxidative-nitrosative stress and apoptosis. Oxidative (superoxide anion and 4-HNE) and nitrosative (protein nitrosylation) stress ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…24 Fannin et al found that increased age in the female F344xBN rat (30 months vs. 6 month) was associated with increases in markers of OS and apoptosis. 25,26 In young rats, ovariectomy has been reported to cause cardiac structural and functional that include cardiac fibrosis and hypertrophy. 27 Ovariectomized rats also exhibit OS and cardiac apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…24 Fannin et al found that increased age in the female F344xBN rat (30 months vs. 6 month) was associated with increases in markers of OS and apoptosis. 25,26 In young rats, ovariectomy has been reported to cause cardiac structural and functional that include cardiac fibrosis and hypertrophy. 27 Ovariectomized rats also exhibit OS and cardiac apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that the number of TUNEL-positive myonuclei, which is an apoptosis marker, was affected by aging, especially during the development and aging phases. Fannin et al [28] investigated the mitochondria-mediated apoptotic pathway in aging female F344xBN rats and suggested that aging was associated with increases in the Bax/Bcl-2 ratio, caspase-3 activation, and the number of TUNEL-positive myonuclei. Apoptosis has an important homeostatic role in normal, healthy hearts; however, excessive apoptosis leads to pathological, life-threatening heart dysfunction during the aging process [29].…”
Section: Discussionmentioning
confidence: 99%
“…The age-related myocardial dysfunction has important implications with regard to impaired redox homeostasis (Duicu et al 2013;Judge et al 2005). Superoxide radical ions and other ROS are known to be produced as inevitable by-products of normal aerobic metabolism in cardiac tissue, while ROS may have important roles in cellular functions, such as cell signaling; furthermore, it is clear that high levels of ROS cause impaired redox homeostasis (Fanin et al 2013). There is growing evidence that increased mitochondrial ROS formation is particularly harmful for aging cells (Shinmura 2013).…”
Section: Introductionmentioning
confidence: 99%